Sustained virologic response and changes in liver fibrosis parameters following 12-wk administration of generic sofosbuvir and daclatasvir in HIV/HCV-coinfected patients with HCV genotype 4 infection. (11th January 2020) - Cordie, Ahmed; Elsharkawy, Aisha; Abdel Alem, Shereen; Meshaal, Safa; El Akel, Wafaa; Abdellatif, Zeinab; Kamal, Walid; Al Askalany, Mahmoud; Kamel, Sherif; Abdel Aziz, Hossam; Kandeel, Amr; Esmat, Gamal
Abstract: Background: Novel direct-acting antiviral agents have shown great efficacy and tolerability in HCV-monoinfected patients. However, data are lacking regarding their efficacy and safety in HIV/HCV-genotype (GT) 4-coinfected patients. Methods: A single-centre, prospective study including HIV/HCV-GT 4-coinfected patients who were treated with sofosbuvir and daclatasvir (SOF/DCV) was conducted for 12 wk. Sustained virological response (SVR) at week 12 post-treatment (SVR12), adverse events (AEs) and changes in liver stiffness measurement (LSM) at SVR12 in comparison with baseline were evaluated. Results: SVR12 was achieved in 46 of 50 patients (92%). No significant difference in SVR12 was noticed among patients who received antiretroviral therapy (ART) regimens compared with those who did not receive ART regimens or between those with insignificant fibrosis (<F2) and those with significant fibrosis (≥F2) (p = 0.9 and p=0.3, respectively). AEs occurred in 45 (90%) patients. The most frequent AEs were fatigue, headache and nausea. No treatment-related serious AEs or deaths were reported. HIV control was not compromised. LSM, fibrosis 4 score and aspartate aminotransferase-to-platelet ratio index showed a significant decrease at SVR12 when compared with baseline (p=0.0004, p=0.0003 and p<0.0001, respectively). Logistic regression analysis showed no association between baseline variables and SVR12 while significant fibrosis (≥F2) was the only baseline variable that was significantly associated with improvement of LSM at SVR12. Conclusion: SOF/DCV achieved a high SVR12 and was well-tolerated in HIV/HCV-GT 4-coinfected patients.